An improved and robust biometrics-based three factor authentication scheme for multiserver environments - Chaudhry, Shehzad Ashraf; Naqvi, Husnain; Farash, Mohammad Sabzinejad; Shon, Taeshik; Sher, Muhammad (Journal of Supercomputing, 2018)
The rapid advancement in communication technologies enables remote users to acquire a number of online services. All such online services are provided remotely facilitating the users to freely move any where with out disruption of the services. In order to ensure seamless and secure services to the remote user such services espouse authentication protocols. A number of authentication protocols are readily available to achieve security and privacy in remote client server architecture. Most of these schemes are tailored for single server architecture. In such scenario, if a user wants to attain the services provided by more than one servers he has to register with each server. In recent times, multiserver authentication has got much attention, where a user can register once and then can acquire services provided by multiple servers. Very recently, Lu et al. proposed a biometric, smart card and password-based three factor authentication scheme usable for multiserver environments. Furthermore, Lu et al. identified their scheme to resist known attacks. However, the analysis in this paper ascertains that Lu et al.’s scheme is vulnerable to impersonation attack. An adversary registered to the system just after knowing the public identity of a user can impersonate himself as the latter. Then we propose an improvement over Lu et al.’s scheme. Our improvement is more robust than the existing schemes. The security of proposed scheme is substantiated formally along with informal security discussion, while same is also validated using a popular automated tool ProVerif. The analysis confirms that proposed scheme achieves mutual authentication and is robust against known attacks. In addition, the proposed scheme does not incur any extra computation as compared with Lu et al.’s scheme.
Keywords: Anonymity; Authentication protocols; Communication technologies; Impersonation attack; Multi-server; Multi-server environment; Mutual authentication; Proverif; Anonymity; Authentication; Biometrics; Impersonation attack; Multiserver; ProVerif; Smart card stolen attack